FACTORS AFFECTING THE FINANCIAL SUPPORT OF MILITARY PERSONNEL - Tsiukalo, L.; Tumanska, M. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
Based on the analysis of theoretical sources and the legislative framework, the factors influencing the financial support of military personnel are proposed. Four groups of factors affecting the financial support of military personnel are identified, namely: a) military, b) political, c) economic and d) social. These groups of factors are interconnected and based on them, the system of monetary support for military personnel is formed. However, at different times and under different conditions, a certain factor is dominant. Motives for military service in the Armed Forces of Ukraine were analyzed, and three groups of motives were identified, namely: a) professional, b) emotional, and c) material. These groups of motives are not mutually exclusive. Financial support for military personnel is state-guaranteed funds that stimulate qualified military personnel. It is determined depending on the position, military rank, duration, intensity, conditions of military service, qualifications and other factors. The influence of the financial support of military personnel on the effectiveness of their performance of official duties is substantiated. In modern conditions, the financial support of military personnel is one of the factors of ensuring the state sovereignty of Ukraine, as it has a positive effect on the number of military personnel, the effectiveness of the service of military personnel who directly or indirectly participate in the protection and defense of the country. Further research will be aimed at the further study of the financial support of military personnel, the study of the effectiveness of the existing system of financial support of the Armed Forces of Ukraine, the development of recommendations regarding the new system of remuneration of military personnel in order to achieve the goals of the financial support of the Armed Forces of Ukraine.